Investigation of HDPE Plastic Waste Aggregate on the Properties of Concrete - Al Bakri, A. M Mustafa; Tamizi, S. Mohammad; Rafiza, A. R; Zarina, Y (Journal of Asian Scientific Research, 2011)
Quantities of polymer wastes have increased in recent years due to increases in industrialization and the rapid improvement in the standard of living. In Malaysia, most polymer wastes are abandoned and not recycled, causing serious problems, such as the waste of natural resources and environmental pollution. Polymer products, such as synthetic fibers, plastics, and rubber, are made from petrochemical compounds, and they degrade extremely slowly in the natural environment. Plastic materials are not easily biodegradable even after a long period. In fact, a wide variety of waste materials can be utilized as inert materials in the cement matrix. In this research, trash bag plastics were used as the polymer waste types high-density polyethylene (HDPE) for preparation of polymer concrete (PC). The aim of this work was to study the properties of polymer HDPE and to characterize this polymer as a potential replacement for coarse aggregate in concrete. Heating was conducted at five different temperatures, i.e., 160 °C, 170 °C, 180 °C, 190 °C, and 200°C. Five compositions of coarse aggregate with different crushed stone: HDPE waste volumetric ratios were used, i.e., 0:100, 15:85, 30:70, 45:55, and 60:40. Comparisons of conventional concrete with polymer waste as coarse aggregate were conducted. The effects of polymer wastes on the workability and strength of the concrete with fresh and hardened concrete tests were analyzed. Compressive strength was measured after 28 days, and it was found that the PC was suitable for non-structural usage. As for the cost analysis, the results showed that the PC was more cost effective than conventional concrete.